2021
DOI: 10.3390/medicina57090926
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and In-Hospital Management and Outcomes of Acute Myocardial Infarction

Abstract: Background and Objectives: Contemporary data on the prevalence, management and outcomes of acute myocardial infarction (AMI) in relation to body mass index (BMI) are limited. Materials and Methods: Using the National Inpatient Sample from 2008 through 2017, we identified adult AMI hospitalizations and categorized them into underweight (BMI < 19.9 kg/m2), normal BMI and overweight/obese (BMI > 24.9 kg/m2) groups. We evaluated in-hospital mortality, utilization of cardiac procedures and resource utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…13,34 Patients with extreme BMI (<18.5 and >40kg/m2) are also at increased risk of adverse outcomes after PCI. 48 Patients post-PPCI who were treated for more than 7 days had an average BMI of 24.22 kg/m2. 13 There is a relationship between obesity and coronary atherosclerosis, with hemodynamic, metabolic, and inflammatory factors as well as oxidative stress contributing to the development of cardiovascular disease in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,34 Patients with extreme BMI (<18.5 and >40kg/m2) are also at increased risk of adverse outcomes after PCI. 48 Patients post-PPCI who were treated for more than 7 days had an average BMI of 24.22 kg/m2. 13 There is a relationship between obesity and coronary atherosclerosis, with hemodynamic, metabolic, and inflammatory factors as well as oxidative stress contributing to the development of cardiovascular disease in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 The underlying cause is unclear; still, some hypotheses exist suggesting that the relevant studies had older underweight patients and more male patients. 44 Furthermore, a more detailed prognosis requires the assessment of central obesity by measuring waist circumference. 45 …”
Section: Discussionmentioning
confidence: 99%
“…For example, obese individuals may develop type II diabetes mellitus due to insulin resistance [ 36 , 37 ], followed later by adverse lipid profiles, eventually leading to CAD or other severe cardiovascular complications [ 38 , 39 ]. However, even though obese individuals are more prone to CAD, there have been reports of better prognosis in patients with high BMI after coronary artery occlusion or acute myocardial infarction [ 40 , 41 ]. Underweight individuals (BMI < 18.5 kg/m 2 ) with acute coronary syndromes exhibited a paradoxically worse prognosis than overweight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study demonstrated that patients admitted to hospital for management of acute myocardial infarction had better prognosis when they were overweight or obese, followed by those with normal weight, while underweight patients exhibited the worst prognosis. The authors of that study reported that most of the underweight patients were older with more comorbidities compared to overweight patients, offering a probable explanation for this paradoxical finding [ 40 ].…”
Section: Discussionmentioning
confidence: 99%